2015
DOI: 10.1590/1809-4430-eng.agric.v35n3p528-541/2015
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade do corte basal de cana-de-açúcar utilizando-se de três modelos de facas

Abstract: RESUMO:A colheita mecanizada de cana-de-açúcar é uma tendência crescente e irreversível ao setor canavieiro, devido à sua maior operacionalidade durante os turnos diurno e noturno, em razão das leis ambientais e trabalhistas ligadas a esta operação. Entretanto, o grande desafio deste sistema é a melhoria do mecanismo de corte de base, uma vez que esse mecanismo é capaz de causar elevados índices de danos e abalos nas soqueiras quando associado ao desgaste das facas do mecanismo de corte basal. Diante do expost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 13 publications
1
15
0
2
Order By: Relevance
“…Several studies used the SPC as a tool to assess the quality of the mechanical harvesting process and demonstrate a potential tool to be applied in agriculture (Noronha et al, 2011;Chioderoli et al, 2012;Bertonha et Santos et al 4895 al., 2014;Voltarelli et al, 2015), mainly because of the possibility of correcting failed points, which considerably increases the final quality of the process, as well as the net return to agricultural activity. From that exposed, it presupposes that the losses in mechanical harvesting of peanuts have temporal variability that can be reduced with the use of automatic guidance, which is aimed at evaluating the quality of digging mechanized peanuts with and without the use of autopilot at sowing and digging, using the losses as quality indicators through statistical process control techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies used the SPC as a tool to assess the quality of the mechanical harvesting process and demonstrate a potential tool to be applied in agriculture (Noronha et al, 2011;Chioderoli et al, 2012;Bertonha et Santos et al 4895 al., 2014;Voltarelli et al, 2015), mainly because of the possibility of correcting failed points, which considerably increases the final quality of the process, as well as the net return to agricultural activity. From that exposed, it presupposes that the losses in mechanical harvesting of peanuts have temporal variability that can be reduced with the use of automatic guidance, which is aimed at evaluating the quality of digging mechanized peanuts with and without the use of autopilot at sowing and digging, using the losses as quality indicators through statistical process control techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a sugarcane crop can be classified as favorable to harvest initially but, after harvester passing, this condition can be changed by the action of row dividers. Although Voltarelli et al (2015) and Noronha et al (2011) stated that sugarcane upright position is ideal for mechanized harvesting, these authors did not assess field lodging level. Given the sugarcane harvester mechanism, another factor favoring ratoon damages and losses is plant position in relation to the harvester path.…”
Section: Resultsmentioning
confidence: 99%
“…Ratoon losses were assessed by a manual force applied to ratoons, estimating their mobilization within the soil and classifying it according to the intensity of force needed to move/tumble stems to the sides (strong, medium, and weak). Based on this classification, loss index (LI) was classified into three levels: strong (0.66 < LI ≤1.0), medium (0.33 ≤ LI ≤0.66), and weak (0.00≤ LI <0.33), based on the method of Voltarelli et al (2015), so that the greater the mobilization, the greater the loss of ratoons. Loss index was estimated as per [eq.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies used control charts to identify the occurrence of special causes Silva et al, 2013b;Voltarelli et al, 2013Voltarelli et al, , 2014Voltarelli et al, , 2015Noronha et al, 2011;Custodio et al, 2012). Chioderoli et al (2012) reported that control charts can be used efficiently to evaluate the quality of Felipe B. F. de Lima, Michel A. F. da Silva, Rouverson P. da Silva, et al Eng.…”
Section: Introductionmentioning
confidence: 99%